Study on positive psychology from 1999 to 2021: A bibliometric analysis - Wang, Feifei; Guo, Jia; Yang, Guoyu (Frontiers in Psychology, 2023)
Objective: Positive psychology is a revolution in the science of psychology as well as a new milestone in the development of human society. The purpose of the study was to use bibliometrics and visual analysis to assess the current state and trends in positive psychology research. Methods: The Web of Science Core Collection was searched for 4,378 papers on positive psychology between 1999 and 2021. The features of positive psychology research were analyzed using Microsoft Excel 2013, VOSviewer (1.6.17), and CiteSpace (5.8.R1). Results: The findings demonstrate a steady growth in positive psychology publications from 1999 to 2021. The United States (1,780) and Harvard University (104), respectively, were the most productive nations and organizations in this subject. Frontiers in Psychology was the most productive journal (288), while the Journal of Personality and Social Psychology had the most co-citations (8,469). Seligman MEP was the most influential author, with 3350 citations and 5020 co-citations. References such as Bolier L. (2013), Seligman MEP. (2005), Seligman MEP. (2000), Sin NL. (2009), and Peterson C. (2004) have the highest citations, suggesting that these papers provide the foundation for the growth of this discipline. The systematic review, character strengths, positive psychology intervention, language pleasure, and the COVID-19 pandemic are the focal points of research and development developments in this discipline. Conclusions: These findings have helped researchers in positive psychology find new ways to collaborate with partners, hot topics, and research frontiers.